2016
DOI: 10.1158/1538-7445.am2016-1483
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1483: MT-3724, an engineered toxin body targeting CD20 for non-Hodgkin's lymphoma

Abstract: Molecular Templates has developed engineered toxin bodies (ETBs), potent recombinant immunotoxins that combine the specificity of an antibody fragment with the powerful direct cytotoxicity of the Shiga-like toxin A subunit to specifically destroy target expressing cells. The use of other immunotoxins and antibody-drug conjugates is limited to targets with tumor-specific cell surface expression that efficiently internalize. The ETB scaffold has been designed to overcome this limitation and promote forced intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study also included a dose expansion phase, which was added to address a potential interaction between circulating rituximab and MT-3724 efficacy ( 11 ). This additional dose-expansion evaluated safety and efficacy of MT-3724 in serum rituximab-negative patients with DLBCL treated at the MTD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also included a dose expansion phase, which was added to address a potential interaction between circulating rituximab and MT-3724 efficacy ( 11 ). This additional dose-expansion evaluated safety and efficacy of MT-3724 in serum rituximab-negative patients with DLBCL treated at the MTD.…”
Section: Methodsmentioning
confidence: 99%
“…MT-3724, a novel ETB construct comprised of an anti-CD20 single-chain variable fragment genetically fused to SLT-A, is capable of binding to and forcing internalization of CD20, a cell surface protein that does not otherwise internalize; subsequently, MT-3724 is routed to the endoplasmic reticulum and induces potent direct cell kill via permanent inactivation of ribosomes ( 10 ). Preclinical in vitro studies have demonstrated that MT-3724 specifically targets and directly kills CD20 + cells, resulting in decreased tumor growth in the Daudi-Luc xenograft murine model ( 11 ).…”
Section: Introductionmentioning
confidence: 99%